Infection of the Biliary Tree. Bacteriological study of 100 cases obtained by surgery - Florez Sáenz, William (1960)
The role that infection plays in the etiology of cholecystitis, has received extensive attention in recent years, not only in colecistisis but also recurrence of symptoms of cholecystectomy patients, keeping in mind these facts and the importance increasingly has to physician and surgeon for complete knowledge of the vesicular diseases so prevalent is that submitted the following contribution to the study of such conditions in its infectious aspect in our midst.